The time between fiction and philosophy: on the History of the siege of Lisbon, by José Saramago - Lachat, Marcelo (Estudos Avançados, 2020)
The purpose of this paper is to discuss the concept of time in the History of the Siege of Lisbon (1989), by José Saramago. To this end, based a reading of the novel, we turn to philosophical considerations - by Augustine, Kant, Nietzsche, Bergson, Cioran and Koselleck - about time and history. Thus, we intend to highlight and analyze the temporal strata of Saramago’s History based on the relationships between fiction and philosophy.